Analisis Penilaian Kinerja Terhadap Rasionalitas Dosen pada 114 Perguruan Tinggi Swasta (PTS) Wilayah Kopertis XIII Provinsi Aceh dengan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Munawir, Munawir (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2018)
This research aims to make a sort 104 University in Region XIII Kopertis Aceh Provincewith the method Technique for Order Preference by Similarity to Ideal Solution(TOPSIS) against the ratio of lecturers and students. TOPSIS is one method that can beused to solve the problem of Fuzzy MADM. This research takes into account all thecriteria that support decision making in order to help speed up and facilitate thedecision-making process and do a minimal quantity of perangkingan especially thelecturer at a college. Based on research results, calculation of TOPSIS begins withforming a decision matrix is normalized, then continued with a decision matrixweighting normalization. The step is done to determine the ideal solution matrix ofpositive and negative solution is ideal. The last stages of the method is to calculate thevalue of the preference of each alternative (Vi) in order to get the final results, the mosthigh value Vi shows the best alternative. Based on the end result then sorted 25 Colleges(PTS) is Locality Kopertis XIII Aceh at its best.